A new sesquiterpene lactone from yacon leaves. Issue 1 (2nd January 2017) - Yuan, Ying; Win Aung, Khin Khin; Ran, Xiao-Ku; Wang, Xiao-Tong; Dou, De-Qiang; Dong, Feng
Abstract: The chemical constituents of 60% EtOH extract of yacon leaves were separated to yield a new compound, together with four known compounds, which were isolated for the first time from yacon. The new compound was characterised and named as chlorodalin (1 ) on the basis of NMR (1D and 2D), HR-MS and other spectral methods. The cytotoxic activities of1 –5 were evaluated on two human tumour cell lines and the new compound showed significant cytotoxic activity. Graphical Abstract: